Association between neighborhood built environment and health-related fitness: a systematic review protocol. Issue 9 (14th September 2021) - Frehlich, Levi; Christie, Chelsea; Ronksley, Paul; Turin, Tanvir C.; Doyle-Baker, Patricia; McCormack, Gavin
ABSTRACT: Objective: The objective of this review is to summarize the current literature on the association between the neighborhood built environment and components of health-related fitness. The findings may be useful for policy-makers and health professionals to inform the development of health-supportive neighborhood built environments. Introduction: There is accumulating evidence linking neighborhood built environments to health, including physical activity and chronic health conditions, yet little is known about the potential links between the built environment and health-related fitness. Although physical activity and health-related fitness are intimately linked, health-related fitness is thought to be a more proximate and stronger correlate of health. Understanding how the built environment influences health-related fitness will allow better health-promoting urban design and population-level interventions. Inclusion criteria: Published and unpublished evidence will be included if it has a quantitative component and the sample includes adults aged 18 years or older, with no physical disabilities or health issues that may affect health-related fitness. The exposure of interest will be objectively measured and self-reported neighborhood built characteristics. The outcome of interest will be objectively measured and self-reported components of health-related fitness (ie, morphological, muscular, motor, and cardiorespiratory fitness). Methods: We will follow the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Databases used in the search will include MEDLINE, Embase, CINAHL, Web of Science, SPORTDiscus, Environment Complete, and Transport Research International Documentation with no date or language restrictions. Two independent reviewers will screen titles and abstracts, and assess full-text studies against the inclusion criteria. Study quality will be assessed by two independent reviewers using the critical appraisal tools from JBI. A narrative approach will be used to synthesize the study findings; if data permit, a meta-analysis will be completed. Systematic review registration number: PROSPERO CRD42020179807